КЛАСТЕРНЫЙ АНАЛИЗ БАЗЫ ДАННЫХ ПАРАМЕТРОВ ОРБИТ ИСЗ - Шакун, Л. С.; Кошкин, Н. И. (Одеські астрономічні публікації, 2011)
Cluster analysis of database of orbit parameters of artificial satellites. L.Shakun, N.Koshkin. The relational base of orbital parameters of near-Earth space objects (SO) is created. For 2007 it is led correlative and cluster analysis on variations of values В* for 4.5 thousand of low-Earth orbit (LEO) objects. Clusters LEO with similar character of atmospheric drag are selected.